Effect of Adding Red Propolis to Edible Biodegradable Protein Films for Coating Grapes: Shelf Life and Sensory Analysis - Filgueiras, Cristina Tostes; Fakhouri, Farayde Matta; Garcia, Vitor Augusto dos Santos [UNESP]; Velasco, José Ignacio; Nogueira, Gislaine Ferreira; Ramos da Silva, Luan; Oliveira, Rafael Augustus de (MDPI, 2024)
Red propolis is an active ingredient of great nutritional interest which offers numerous benefits as an antioxidant and antimicrobial agent. Thus, the objective of this research was to evaluate the application of an edible and antimicrobial gelatine coating containing red propolis to increase the shelf life of grapes. Gelatine films with an addition of 5, 10, 15, 20 and 25% of red propolis extract were produced to evaluate their antimicrobial activity using the disk diffusion test in solid media. The films with 25% red propolis extract showed antimicrobial activity against the bacteria Staphylococcus aureus and Pseudomonas aeruginosa. The grapes were coated with pure gelatine, without a plasticizer and with gelatine with 25% red propolis and then stored for 1, 4, 10, 19 and 25 days at temperatures of 25 °C and 5 °C. The results showed that the gelatine coating with propolis reduced the mass loss of grapes stored at 25 °C for 19 days by 7.82% and by 21.20% for those kept at 5 °C for 25 days. The pH, total titratable acidity, soluble solids and color of the grapes increased due to the ripening process. Furthermore, the sensory acceptability indexes of the refrigerated grapes with coatings were superior (>78%) to those of the control samples (38%), proving the effectiveness of the coatings in maintaining the quality of grapes during storage.
Keywords: biodegradable films; conservation; edible covering; fruit; natural antimicrobial agent; post-harvest technology; sensory analysis; shelf life